Budaya “Mejejahitan” Bagi Wanita Sebagai Kearifan Lokal di Bali - Putu Agus Windu Yasa Bukian; Wayan Sujana (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
Culture is local wisdom that continues to be implemented today. Bali is no exception, where mejejahitan culture is a tradition that continues to be carried out by Hindu women in Bali. The purpose of this article is to identify the characteristics of Balinese women, the types of jejahitan that can be done by Balinese women, and then practice in making offerings. This type of research is the quantity across-sectional sectional approach. The population in this study were Hindu women in Bungkulan Village, a sample of 194 respondents was taken using a simple random sampling technique, the instrument in this study was a questionnaire related to the characteristics, types,of jejahitan, and the practice of offerings carried out. The analysis was carried out bivariate with computerization. The results of the study found that the average age of women was 44 years, 30.4% were elementary school graduates, 45.9% worked on canang sari and 54.6% were still not good at making offerings. The conclusion ion is that Canang sari is the easiest sewing to do and the role of women is very important in the religious process in Bali. So that the implementation of Balinese culture emphasizes the presence of women to help complete the preparation of the ceremony.